The subfamily Cercidoideae (Fabaceae Lindl.) in the Chapada do Araripe, Northeast Brazil - Ferreira Da Cruz, Mariana; Bezerra Dos Santos, Antonio Carlito; Da Silva Sampaio, Valéria; Calixto Júnior, João Tavares; de Almeida Souza, Marta Maria; de Melo Alcântara, Bruno; Soares Da Silva, José Anderson; Bezerra Loiola, Maria Iracema; Pessoa Da Silva, Maria Arlene (Phytotaxa, 2024)
The Fabaceae family holds the greatest floral diversity and number of species in Brazil, having high economic, ecological, and medicinal importance, and is currently divided into six subfamilies. This study consisted of a survey and description of species of the Cercidoideae subfamily occurring in the Chapada do Araripe, Northeast Brazil. Nine species belonging to the genera Bauhinia and Schnella were cataloged, and one species (B. forficata) is presented here as a new record in Ceará state. This article provides botanical identification keys, data on phenology, and distribution, and a geographic distribution map aiming to expand knowledge of the regional flora and to support preservation actions in the Chapada do Araripe.